2021
DOI: 10.1513/annalsats.202007-884oc
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validity Assessment of a Chronic Obstructive Pulmonary Disease Knowledge Questionnaire in Low- and Middle-Income Countries

Abstract: Rationale: The majority of the morbidity and mortality related to chronic obstructive pulmonary disease (COPD) occurs in low-and middle-income countries (LMICs). Despite the increasing burden of COPD, disease-specific knowledge among healthcare workers (HCWs) and patients in LMICs remains limited. COPD knowledge questionnaires are valid and reliable tools to assess COPD knowledge and can be employed in settings with limited health literacy.Objective: To develop and assess validity and reliability of a COPD kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
3
0
3
Order By: Relevance
“…Moreover, we argue that continuous patient-centered health education efforts are imperative to raise patients’ awareness to COPD screening services and thus agency in self-management. 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we argue that continuous patient-centered health education efforts are imperative to raise patients’ awareness to COPD screening services and thus agency in self-management. 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…These strategies have been shown to improve knowledge, quality of life, and health-related outcomes. 36 Few education studies for patients with COPD include the importance of vaccination, 10 which may impact outcomes such as severe respiratory infection, 29 , 37 because other items such as drug treatment and knowledge about the disease are considered to be more critical. Our findings are consistent with the literature, which has shown that integrated care programs, which include education about the disease as an integral part of the care model adapted to each latitude and with different educational methodologies, improve the level of patients’ knowledge and, in many cases, are associated with better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Dies könnte Informationen darüber geben, auf welchen Gebieten die Patienten mit spezifischem Wissen versorgt und gegebenenfalls geschult oder in ihrem Verhalten beraten und unterstützt werden sollten. Die derzeit verfügbaren und publizierten internationalen Fragebögen [1][2][3][4][5][6][7][8] umfassen teils sehr viele Fragen (bis zu 65), was ihren Einsatz in der klinischen Praxis einschränkt, oder sind an länderspezifische Gegebenheiten angepasst. Die deutschsprachigen Fragebögen sind hingegen i. d. R. nicht publiziert und enthalten ebenfalls teils Elemente, die auf lokale Schwerpunkte und Bedürfnisse zugeschnitten erscheinen.…”
Section: Introductionunclassified
“…Es steht zu vermuten, dass ein niedrigeres Alter und eine höhere Schulbildung eine höhere Gesundheitskompetenz der Patienten begünstigten, indem jüngere und besser gebildete Patienten die Erklärungen und Ratschläge des Gesundheitspersonals besser verstehen und internalisieren, und folglich auch angemessener handeln können. Dass der bekannte Zusammenhang eines niedrigeren Alters und einer höheren Schulbildung mit einer höheren Gesundheitskompetenz [8,16,18,[19][20][21] auch in den vorliegenden Daten beobachtet wurde, spricht erneut für die Validität der Daten und die Relevanz der Fragen.…”
unclassified
See 1 more Smart Citation